Predictors of sustained response and effects of the discontinuation of anti‐calcitonin gene related peptide antibodies and reinitiation in resistant chronic migraine. (13th February 2022) - Iannone, Luigi Francesco; Fattori, Davide; Benemei, Silvia; Chiarugi, Alberto; Geppetti, Pierangelo; De Cesaris, Francesco
Abstract: Background and purpose: Guidelines for migraine prophylaxis suggest stopping medication after 6–12 months to reevaluate treatment appropriateness. The Italian Medicines Agency set a mandatory regulation to stop anti‐calcitonin gene related protein (CGRP) pathway monoclonal antibody (anti‐CGRP mAb) treatments for 3 months after 12 months of treatment. Herein, the effects of discontinuation and retreatment of anti‐CGRP mAbs in resistant chronic migraine patients are assessed, evaluating predictive factors of sustained response. Methods: This was a monocentric prospective cohort study, enrolling 44 severe (resistant to ≥3 preventive treatments) chronic migraine patients (all with medication‐overuse), treated with erenumab (54.5%) or galcanezumab (45.5%) for 12 months, who discontinued treatment for 3 months and then restarted for 1 month. Results: Overall, patients reported an increasing deteriorating trend during the 3 months of discontinuation. Monthly migraine days, number of analgesics, days with at least one analgesic used, a ≥50% response rate (reduction in monthly migraine days), and Migraine Disability Assessment Score and Headache Impact Test 6 total score, remained lower than baseline values, but increased compared to month 12 of treatment. All outcome measures decreased again during the month of retreatment. Patients who did not meet criteria for restarting treatment had a lower Migraine Disability Assessment Score ( p  = 0.03) and Headache Impact Test 6 ( p  = 0.01) score at baseline and better outcome measures during discontinuation compared to patients who restarted treatment. Conclusions: In most patients, the 3‐month discontinuation of anti‐CGRP mAbs resulted in progressive migraine deterioration that was rapidly reverted by retreatment. However, one‐quarter of patients who reported better quality of life indices before treatment showed a sustained benefit during discontinuation and did not need retreatment. Abstract : All outcome measures decreased again during the month of retreatment. Patients who did not meet criteria for restarting treatment had lower Migraine Disability Assessment Score and Headache Impact Test 6 score at baseline and better outcome measures during discontinuation compared to patients who restarted treatment.